Democratic deconsolidation in East Asia: exploring system realignments in Japan, Korea, and Taiwan. Issue 1 (2nd January 2021) - Chull Shin, Doh
ABSTRACT: This study explores how and why the citizenries of Japan, Korea, and Taiwan engage in deconsolidating the liberal democratic system in which they live. For this exploration, the study conceptualizes democratic deconsolidation as a two-phase psychological movement and analyses it as the realignment of system affiliation. The analysis of the Asian Barometer Survey recently conducted in these countries reveals that pluralities of their citizenries are psychologically disposed to realign themselves with a hybrid or autocratic system. It also reveals that democratic learning and socioeconomic modernization, two significant influences on democratic consolidation, do little to keep East Asians from joining in the deconsolidation movement. These findings suggest that the deconsolidation of democracy not be equated with a reversal of its consolidation.